“Me” in Other Realms: Reinterpretations of Identity in Fantasy Fiction - Barbora Vinczeová (Ksiegarnia Akademicka Publishing, 2017)
This article presents the notion of identity as perceived in Tanith Lee’s awardwinning novel Death’s Master. It focuses on the four main relations between identity and other concepts found in the novel, often resulting in identity conflict. It also addresses the traditional and non-traditional perceptions of the given phenomena, e.g. rejection of motherhood, gender fluidity, collective identity and the identity of abstract notions personified, such as death. Our goal is to examine the different concepts of “self” as related to social standing, sexuality, gender or nature. The overall aim of the article is to present how the author reworks the concepts of traditional identity in relation to stereotypical representations of the characters.